Phospholipid flippases: building asymmetric membranes and transport vesicles - Sebastian, Tessy T. (2011)
Phospholipid flippases in the type IV P-type ATPase family (P4-ATPases) are essential components of the Golgi, plasma membrane and endosomal system that play critical roles in membrane biogenesis. These pumps flip phospholipid across the bilayer to create an asymmetric membrane structure with substrate phospholipids, such as phosphatidylserine and phosphatidylethanolamine, enriched within the cytosolic leaflet. The P4-ATPases also help form transport vesicles that bud from Golgi and endosomal membranes, thereby impacting the sorting and localization of many different proteins in the secretory and endocytic pathways. At the organismal level, P4-ATPase deficiencies are linked to liver disease, obesity, diabetes, hearing loss, neurological deficits, immune deficiency and reduced fertility. Here, we review the biochemical, cellular and physiological functions of P4-ATPases, with an emphasis on their roles in vesicle-mediated protein transport.